1991
DOI: 10.1111/j.1432-1033.1991.tb16186.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the β‐glucosidase gene bglA of Clostridium thermocellum

Abstract: The nucleotide sequence of the Clostridium thermocellum gene bglA, coding for the thermostable j-glucosidase A, has been determined. The coding region of 1344 bp was identified by comparison with the N-terminal amino acid squence of recombinant b-glucosidase A purified from Escherichiu coli. The deduced amino acid sequence corresponds to a protein of 51482 Da. The coding region is flanked by putative promoter and transcription terminator sequences. The protein is unrelated to P-glucosidase B of C . thermocellz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 55 publications
2
53
0
2
Order By: Relevance
“…LPH is synthesized as a single-chain 215-245 kDa precursor comprising four tandemly repeated domains [2][3][4][5][6][7][8]. These show sequence similarity with the type 1 family of glycosyl hydrolases (T1GH family), a family of proteins that includes single-domain enzymes present in micro-organisms (see [9,10] and references therein] and plants [11][12][13], and in the liver of mammals [14]. The T1GH family also comprises multi-domain proteins expressed in the intestine of non-mammalian vertebrates and in invertebrates, but their sequences have not been fully determined [15].…”
Section: Introductionmentioning
confidence: 99%
“…LPH is synthesized as a single-chain 215-245 kDa precursor comprising four tandemly repeated domains [2][3][4][5][6][7][8]. These show sequence similarity with the type 1 family of glycosyl hydrolases (T1GH family), a family of proteins that includes single-domain enzymes present in micro-organisms (see [9,10] and references therein] and plants [11][12][13], and in the liver of mammals [14]. The T1GH family also comprises multi-domain proteins expressed in the intestine of non-mammalian vertebrates and in invertebrates, but their sequences have not been fully determined [15].…”
Section: Introductionmentioning
confidence: 99%
“…CSF26G1 cDNA should encode one of the C. speciosus F26G isozymes which might exist as a minor protein in the rhizomes. I~-Glucosidases are known to fall into two distinct families (BGA and BGB) based on their structure similarities rather than their biological roles and substrate specificities [20,21]. The BGA family includes bacterial ~-glucosidases, archaebacterial I~-galactosidase, plant thioglucosidases, and human lactase-phlorizin hydrolase, while the BGB family includes fungal and rumen bacterial I~-glucosidases [18,21].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the N-terminal region of the multiple alignment groups together the well known sequence motifs [2]. Legler et al [21] observed that the conduritol B-epoxi inhibitor bound to the Asp residue of the SDW motif in Aspergillus wentii.…”
Section: Fig 1 (Cord)mentioning
confidence: 99%
“…His, Glu and Asp are the amino acids thought to be involved in enzymatic hydrolysis using an acid catalytic mechanism [2]. Because of their biotechnological importance, a number of j?-glucosidase genes have been cloned and attempts at organizing /3-glucosidase families and domains have been reported [3,4].…”
Section: Introduction P-glucosidasesmentioning
confidence: 99%